İRADEDE DUYGUNUN ETKİSİNE GENEL BİR BAKIŞ - Nurten Gökalp (Felsefe Dünyası)
There are different views in philosophy related with the human decision and will. While one of them defends the dominant role of the reason in decision-making; other pays attention to the role of the emotions. Essentially, it is important that the thoughtfully relationship between the reason and the emotions should be taken into consideration in philosophy. But this thought disappears in modern philosophy. This article aims at paying attention to this problem in philosophy.